AquaFlora Smart Terrarium: A Self-Sustaining Internet of Things (IoT)-based Terrarium for Smart Ecosystem Management - Irushan Bandara, A.M.T.; Mohamed Halip, N. H.; Purnshatman, Tatchanaamoorti; Mohd Yusoff, Nurulanis; Mohamed Halip, Mohd Hazali (Society of Visual Informatics, 2025)
Using Internet of Things (IoT) technology in smart terrariums is a growing trend that aligns with the move towards more automated and better- well-managed ecosystem gardening. AquaFlora Smart Terrarium is a state-of-the-art system designed to create and maintain the perfect environment for various plants. It features a network of sensors, actuators, and electronic components, all orchestrated by an ESP32 microcontroller. The system leverages four actuators to control light, humidity, irrigation, and cooling, ensuring optimal conditions for plant growth. Three sensors, which are the Capacitive Soil Moisture Sensor, DHT22, and BH1750FVI to monitor soil moisture, temperature, humidity, and light intensity, providing real-time data to the microcontroller. The terrarium can be conveniently controlled via a mobile app and Node-RED, allowing for remote monitoring, control, and automation through Firebase and MQTT. Node-RED visualization of sensor data over a 10-hour period demonstrated the effectiveness of the automatic mode in maintaining stable plant conditions. Soil moisture remained above 60%, temperature ranged between 30.1°C and 33.1°C, humidity between 69.10% and 74.00%, and light intensity between 23 Lux and 175 Lux. The AquaFlora Smart Terrarium represents a significant innovation in plant care, offering a reliable and automated solution to create and sustain the ideal environment for healthy plant growth.